INFLUENCE OF PRINCIPALS’ INSTRUCTIONAL SUPERVISION ON STUDENTS’ ACADEMIC ACHIEVEMENTM IN KENYA CERTIFICATE OF SECONDARY EDUCATION IN BUNGOMA NORTH SUB-COUNTY - Samuel , Mutoro M.; Musera, Goeffrey; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
A secondary education is a necessary requirement for entrance to institutions of higher learning and extra skill training. The role of a principal in shaping the teaching and learning experience of students is crucial, highlighting the importance of evaluating their instructional leadership abilities. The objective of this study was to investigate the influence of Principals’ instructional supervision on academic achievement in KCSE in Bungoma North Sub-County, Kenya. The research approach employed in this study was descriptive in nature. The target population consisted of 2,215 individuals, including 2,125 pupils, 84 instructors, and 6 principals. These individuals were selected from public secondary schools located in Bungoma North Sub County. The research employed a stratified random sampling method, with a sample size of 331 chosen using the Krejcie and Morgan table (1970). Structured questionnaires and interview guides were employed as the primary instruments for data collection in this investigation. The instrument underwent a validation process overseen by the experts in the area under study. The determination of the instrument's reliability was accomplished by means of a pilot study. The Cronbach's alpha coefficient for the questionnaires used in this study was found to be 0.79 for teachers and 0.78 for students. These values indicate that the instrument used to measure the variables in this study can be considered reliable. This finding suggests that the instrument had a high level of reliability. The analysis of quantitative data involved the use of descriptive statistics, which were then presented in tabular form. On the other hand, the analysis of qualitative data followed a thematic approach, with themes and sub-themes identified and presented through the use of quotations. The study established that there is a statistically significant positive correlation Principals’ instructional supervision on students’ academic achievement in Kenya Certificate of Secondary Education in Bungoma North Sub-County. Hence, it can be inferred that the implementation of proficient principals' instructional supervision has a positive impact on academic performance in the Kenya Certificate of Secondary Education.